Adult Rhabdomyoma of the Larynx - Pinho, Márcia Monteiro; de Carvalho e Castro, Jair; Ramos, Rosana Grandelle (International Archives of Otorhinolaryngology, 2013)
Introduction Rhabdomyoma is a rare benign tumor derived from skeletal muscles. Laryngeal rhabdomyomas are even rarer, with only approximately 40 reported cases in world literature. Laryngeal rhabdomyomas usually are seen as masses covered by mucosa. They are often solitary asymptomatic tumors, but symptoms such as hoarseness can occur. The radiologic features are usually those typical of benign neoplasms, showing well-delineated borders. The differential diagnoses for laryngeal masses include cysts, laryngoceles, and benign and malignant neoplasms. The diagnosis is usually made using histopathologic findings, but in some cases some difficulties can be found. Immunohistochemical staining is of great value in the differentiation of similar tumors. Treatment of rhabdomyoma is surgical excision.Objective To describe a case of rhabdomyoma of the larynx attended at Santa Casa de Misericórdia do Rio de Janeiro.Case Report A 35-year-old man presented with progressive hoarseness in the preceding year. Laryngoscopy showed a large submucosal tumor at the supraglottic region of the larynx. The neck computed tomography scan confirmed the submucosal mass, with distinct borders. The patient was taken to the operating suite, where endoscopic extirpation of the mass was performed. Initial histologic diagnosis was suggestive of paraganglioma, which was not confirmed by studies with immunohistochemical markers, and diagnosis was changed to adult-type rhabdomyoma. The patient recovered well. His voice returned to normal after 3 months.Discussion Although muscle tumors of the larynx are very rare, rhabdomyoma should be considered when there is a submucosal mass in the larynx.
Keywords: immunohistochemistry; laryngeal neoplasms; rhabdomyoma